Catalytic Hydrotreating of Crude Pongamia pinnata Oil to Bio-Hydrogenated Diesel over Sulfided NiMo Catalyst - Yuwadee Plaola; Wanwipa Leangsiri; Kanokthip Pongsiriyakul; Worapon Kiatkittipong; Atthapon Srifa; Jun Wei Lim; Prasert Reubroycharoen; Kunlanan Kiatkittipong; Apiluck Eiad-ua; Suttichai Assabumrungrat (My University, 2022)
This work studied the catalytic activity and stability of Ni-MoS2 supported on γ-Al2O3, SiO2, and TiO2 toward deoxygenation of different feedstocks, i.e., crude Pongamia pinnata oil (PPO) and refined palm olein (RPO). PPO was used as a renewable feedstock for bio-hydrogenated diesel production via catalytic hydrotreating under a temperature of 330 °C, H2 pressure of 50 bar, WHSV of 1.5 h−1, and H2/oil (v/v) of 1000 cm3/cm3 under continuous operation. The oil yield from a Soxhlet extraction of PPO was up to 26 wt.% on a dry basis, mainly consisting of C18 fatty acids. The catalytic activity in terms of conversion and diesel yield was in the same trend as increasing in the order of NiMo/γ-Al2O3 > NiMo/TiO2 > NiMo/SiO2. The hydrodeoxygenation (HDO) activity was more favorable over the sulfided NiMo supported on γ-Al2O3 and TiO2, while a high DCO was observed over the sulfided NiMo/SiO2 catalyst, which related to the properties of the support material and the intensity of metal–support interaction. The deactivation of NiMo/SiO2 and NiMo/TiO2 occurred in a short period, due to the phosphorus and alkali impurities in PPO which were not found in the case of RPO. NiMo/γ-Al2O3 exhibited the high resistance of impure feedstock with excellent stability. This indicates that the catalytic performance is influenced by the purity of the feedstock as well as the characteristics of the catalysts.
Keywords: Hydrodeoxygenation; Deoxygenation; Pongamia; Vegetable oil refining; Ultra-low-sulfur diesel; Catalysis and Hydrodesulfurization Studies